Effect of early life exposure to Ozone and particulate matter on the incidence of eczema in children under 2 years of age - Yuxiu Liang; Fangyi Wang; Shaoqian Lin; Xiaodong Zhao; Shuoxin Bai; Jiatao Zhang; Zhiping Wang (BMC Public Health)
Abstract Background Eczema is more prevalent in children aged 0–2 years, yet the long-term effects of air pollutant exposure during early life on the risk of eczema development remain unclear. Methods We conducted a birth cohort study in Jinan, China, to explore the effect of early life air pollutant exposure on the risk of eczema in younger children. An inverse distance weighting method was used for individual exposure assessment. Binary and multivariate logistic models were used to investigate the effects of air pollutants on eczema, the distributed lag model to find critical windows of exposure, weighted quantile sum model and principal component analysis to explore the combined effects of multiple pollutants. Results The cumulative incidence rate for eczema among 5819 children aged 2 was 19.8%. Exposure to high levels of O3 during pregnancy (OR 1.12, 95%CI 1.06–1.19) and during the first year after birth (OR 1.24, 95%CI 1.03–1.50) increased the risk of eczema. PM2.5−10 during pregnancy, PM2.5 and PM2.5−10 during the first year after birth also increased the risk of eczema. The critical window for O3 and PM exposure was the third trimester and early postnatal period. Moreover, in the joint effect of multiple pollutants, O3 played a dominant role during pregnancy (weighting > 0.3), with a predominantly O3 principal component associated with eczema risk (adjusted OR 1.011, 95% CI 1.007–1.015). Conclusions Early-life exposure to O3 and PM was associated with an increased risk of eczema in children aged 0–2 years, with sensitivity windows appearing to be earlier in life. O3 exposure during pregnancy played a pivotal role in the combined effects of pollutants on eczema risk.